Self-Assessments of Standardized Scalp Massages for Androgenic Alopecia: Survey Results - Robert S. English; James M. Barazesh (Adis, Springer Healthcare, 2019)
Abstract Introduction Standardized scalp massages (SSMs) improve hair thickness in nonbalding men, but their effects on androgenic alopecia (AGA) have not yet been evaluated. The objective of this study was to investigate the effect of SSMs on self-assessed AGA sufferers (SAGASs). Methods Between October 2016 and October 2017, 1899 SAGASs searching online for hair loss treatments beyond AGA management drugs accessed literature explaining SSMs as a potential therapy for AGA, then watched a demonstration video detailing twice-daily, 20-min SSMs segmented by three rotational scalp regions using hand-generated presses, pinches, and stretches. In December 2017, SAGASs were contacted once to participate in a retrospective survey study to assess SSM adherence and hair changes. Age, gender, hair loss region and gradient, diet, supplement and topical use, AGA management drug use, estimations for minutes daily and months of massaging, and self-perceived hair changes were reported. Some participants also submitted photosets documenting hair changes throughout SSM adherence. Results A total of 340 (17.9%) respondents completed the survey, and 327 (17.2%) reported attempting the SSMs. SSM participants reported a median daily massage effort of 11-20 min and mean adherence of 7.4 ± 6.6 months, with 68.9% reporting hair loss stabilization or regrowth. Estimated minutes daily, months, and total SSM effort (i.e., minutes daily × months) were positively associated with self-perceived hair changes. On average, perceived hair loss stabilization and regrowth occurred after 36.3 h of SSM effort. Results did not vary across age, gender, Norwood gradient, or concomitant supplement, topical, finasteride, minoxidil, or microneedling use. However, hair change improvements were marginally lower for participants reporting diffuse versus frontal/temporal or vertex thinning. Conclusions While further research is warranted, these results align with previous findings and suggest the potential for SSMs to improve AGA.